Relationship Among Romantic Jealousy, Self-esteem, Irritability, and Grit in Married and Unmarried Couples - Bedi, Yamini (My University, 2023)
Romantic jealousy is frequently seen as a way for us to show our fear of losing a significant human being that we own; as a result, jealousy is criticized for treating someone else like one's property. While there is some truth to both statements, jealousy is more nuanced. Even if most individuals don't think of their loved ones as their property, they nonetheless get envious when they are ready to lose them to someone else. The primary objective of the current research study was to find out the relationship among romantic jealousy, self-esteem, irritability, and grit in married and unmarried couples. For this, the data was collected from 75 married participants and 75 unmarried people in a relationship. The questionnaire used was the Multidimensional jealousy scale (MJS) by Susan M. Pfeffier to find Romantic Jealousy, for Self Esteem, Rosenberg Self-esteem Scale was used, for irritability, the Sheehan irritability scale was used and the Grit scale by Duckworth was used to measure Grit. Descriptive statistics, Pearson correlation, and stepwise regression were used for analyses of the data. The results revealed that Romantic jealousy was positively correlated with irritability in both married and unmarried people at p <.01 level. Romantic jealousy had a highly negative correlation of -.78 at p < .01 with self-esteem in unmarried people who are in a relationship. Romantic jealousy correlated with all the variables which are self-esteem, grit, and irritability.
Keywords: Romantic Jealousy; Self Esteem; Irritability; Grit